7v+27=-5(v-3)

Simple and best practice solution for 7v+27=-5(v-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7v+27=-5(v-3) equation:


Simplifying
7v + 27 = -5(v + -3)

Reorder the terms:
27 + 7v = -5(v + -3)

Reorder the terms:
27 + 7v = -5(-3 + v)
27 + 7v = (-3 * -5 + v * -5)
27 + 7v = (15 + -5v)

Solving
27 + 7v = 15 + -5v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '5v' to each side of the equation.
27 + 7v + 5v = 15 + -5v + 5v

Combine like terms: 7v + 5v = 12v
27 + 12v = 15 + -5v + 5v

Combine like terms: -5v + 5v = 0
27 + 12v = 15 + 0
27 + 12v = 15

Add '-27' to each side of the equation.
27 + -27 + 12v = 15 + -27

Combine like terms: 27 + -27 = 0
0 + 12v = 15 + -27
12v = 15 + -27

Combine like terms: 15 + -27 = -12
12v = -12

Divide each side by '12'.
v = -1

Simplifying
v = -1

See similar equations:

| 420t-6t^2=3675 | | 3a*2+yx=7 | | 6(x-4)=8x-28 | | 4*(x+1)=2*(5-3x) | | 6+3a= | | 7u-36=3(u-8) | | t^2-60t=-450 | | t^2+60t=-450 | | -3*-3+6+2= | | 14(6x+16)= | | 3*3+6+2= | | 5+7(2b-2b)=5 | | y(25+-.75y)=350 | | x^2+y^2+6x-14y+42=0 | | 42-21x=63-7y | | (6xy+7)dx+(3x^2-2)dy=0 | | 6x+9-x+19= | | 4x+10=-42-8x | | 3n=34 | | 17x-2x=7x+11 | | 7x+13=3x+65 | | 4x+38=180 | | 2(x-3)(x-3)+3=13 | | 2(x-3)+3=13 | | x^4-x^3-2x^2+4x-24=0 | | (X^2+24)= | | 3x^2-11x-3=-x^2 | | Un=5+(0.1n-0.1) | | Un=5+(0.1n+0.1) | | Cos(5x)-cos(9x)=0 | | z^2-(3-2i)z+(5-5i)=0 | | 6x=n+4 |

Equations solver categories